Artificial Intelligence and ESG Performance: Empirical Evidence from Indonesia-Listed Company - Rizky Windar Amelia; Abdul Hadi Hari; Syska Lady Sulistyowatie (LPPM ISNJ Bengkalis, 2025)
Artificial intelligence (AI) quick development has become a major factor in determining how well businesses perform in terms of environmental, social, and governance (ESG). The rapid development of AI is reshaping the global economic, and also social structure, and its wide application empowers the sustainable development of enterprises. This research aims to explore the influence of AI adoption on ESG performance and further assess the mediation effect of ESG performance in the relation between AI adoption and firm value. The research was carried out from 2020 to 2023 on mining sector companies in Indonesia, yielding 225 observational data points. A multivariate analysis was performed utilising partial least squares structural equation modelling (PLS-SEM) to assess the hypothesis. The research findings from hypothesis testing demonstrate that performance, firm size, debt to assets ratio, and also return on equity have a significant positive impact on firm value of mining sector companies. Furthermore, the impact of AI adoption on firm value can be more effectively mediated by ESG performance. By serving as a strategic resource, increasing productivity, and promoting sustainability to satisfy stakeholder expectations, AI improves ESG performance and raises business value. For AI-driven company sustainability, this research promotes standardized policies, management integration, and government support.